THE SECOND GUADALUPIAN SYMPOSIUM AND PROBLEMS OF PERMIAN STRATIGRAPHY - Leven E.Ya.; Leonova T.B.; Kotlyar G.V. (My University, 1997)
The article presents information on the Second Guadalupian Symposium in April 1996 and a meeting of the International Subcommission on Permian Stratigraphy held in its framework. The main subjects for discussion both at the Symposium and the Subcommission meeting were the Standard Stratigraphic Scale for the Permian System and, particularly, the problem of introducing the Guadalupian Series into the scale. The discussions resulted in the recommendation to subdivide the Permian System into three series: the Cisuralian Series with Asselian, Sakmarian, Artinskian, and Kungurian stages, the Guadalupian Series with Roadian, Wordian, and Capitanian stages, and the Lopingian Series with Wuchiapingian and Changhsingian stages.
Keywords: Permian; Guadalupian; Палеозой::Пермская; Paleozoic::Permian::Guadalupian; Paleozoic::Permian; Палеозой::Пермская::Гваделупский